2017
DOI: 10.2147/opth.s136070
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphism 1623 A/G (rs180195) in the promoter of the Thyroglobulin gene is associated with autoimmune thyroid disease but not with thyroid ophthalmopathy

Abstract: BackgroundOur studies over recent years have focused on some new ideas concerning the pathogenesis for the orbital reaction that characterizes Graves’ ophthalmopathy namely, that there are antigens expressed by thyroid tissue and orbital tissue where they are targeted by autoantibodies and/or sensitized T cells, leading to orbital inflammation. While this has been well studied for the thyroid stimulating hormone-receptor, the possible role of another major thyroid antigen, Thyroglobulin (TG), has been largely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…TG is a 660-kDa glycoprotein, which accounts for about 75%-80% of the total thyroid protein [25,26] and deserves to be a major AITDs susceptibility gene. Earlier researches have recognized that TG SNPs were related to the development of AITDs [27][28][29][30][31]. In 2011, Mihaela Stefan et al revealed a new mechanism of interaction between the TG promoter SNP variant with viral infection to AITDs, which laid the foundation for further exploration [32].…”
Section: Discussionmentioning
confidence: 99%
“…TG is a 660-kDa glycoprotein, which accounts for about 75%-80% of the total thyroid protein [25,26] and deserves to be a major AITDs susceptibility gene. Earlier researches have recognized that TG SNPs were related to the development of AITDs [27][28][29][30][31]. In 2011, Mihaela Stefan et al revealed a new mechanism of interaction between the TG promoter SNP variant with viral infection to AITDs, which laid the foundation for further exploration [32].…”
Section: Discussionmentioning
confidence: 99%
“…In one retrospective study, Lahooti et al concluded that vitamin D deficiency was a risk factor for TAO in GD, but not in HT. Thus suggesting a potential different pathogenesis [14]. Unilateral exophthalmos has a wide set of differential diagnosis including orbital primary and secondary neoplasms (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In one retrospective study, Lahooti et al concluded that vitamin D deficiency was a risk factor for TAO in GD, but not in HT. Thus suggesting a potential different pathogenesis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, Lahooti et al found that vitamin D deficiency represents a risk factor for TAO in GD, but not in HT. This might suggest a different pathogenesis of TAO in those two entities [22]. However, these findings require confirmation in larger prospective trials.…”
Section: Discussionmentioning
confidence: 99%